ASSOCIATION BETWEEN SELF-ESTEEM AND LIFELONG LEARNING ORIENTATION AMONG UNDERGRADUATE NURSING STUDENTS AT PRIVATE INSTITUTE SHABQADAR, CHARSADDA, KPK, PAKISTAN (The Research of Medical Science Review, 2025)
Background: Self-esteem, reflecting an individual's perceived value, is vital for psychological well-being. Nursing undergraduates face challenges that require strong self-worth. Lifelong learning is key to professional development, ensuring nurses stay competent. This study explores the link between self-esteem and lifelong learning orientation, emphasizing the importance of both for academic and professional success Objective: To identify the relationship between Self-esteem and Lifelong Learning Orientation Among Undergraduate Nursing Students. Material and method: An Analytical cross-sectional study was conducted at the Shahid College of Nursing, Charsadda, to identify the relationship between Self-esteem and Lifelong Learning Orientation Among Undergraduate Nursing Students. A sample size of 132 undergraduate students was selected using a convenient sampling technique. Data was collected through a valid questionnaire, divided into three parts: Part A, included demographic data; Part B, was included measures of self-esteem using The Rosenberg Self-Esteem Scale; and Part C, which assesses participants' lifelong learning orientation. Results: The study found that most respondents were males (76.5%) aged 18-27 years (84.8%) enrolled in a BSN program (67.4%). A majority (87.1%) exhibited high self- esteem, with a mean score of 24.2, reflecting a positive self-assessment. Similarly, 75.0% demonstrated a strong lifelong learning orientation, with an average score of 30.5. A moderate positive correlation of 0.439 (p<0.01) was found between self-esteem and lifelong learning orientation, suggesting that higher self-esteem is associated with a stronger commitment to lifelong learning. The results highlight the importance of fostering both traits to support personal and academic growth. Conclusion: In conclusion, the study highlights the significant role of self-esteem and lifelong learning orientation in the academic and professional development of nursing students. The findings demonstrate that high self-esteem is associated with a strong commitment to lifelong learning, suggesting that cultivating both traits can positively impact students' growth. The moderate positive correlation between self-esteem and lifelong learning emphasizes the need for educational programs to focus on enhancing both self-esteem and learning orientation. This dual focus can foster personal, academic, and professional success, ultimately contributing to the development of competent, confident, and continuously evolving healthcare professionals